Perubahan Sosial Masyarakat New Normal Pasca Covid-19 - Andi Kumalasari; Ernawati S. Kaseng (PREDESTINATION: Journal of Society and Culture, 2023)
Abstract: The Covid-19 pandemic, which is endemic, has resulted in social changes that occur so quickly, causing people to experience a shift in behavior in everyday life. Based on the core of the problem, this paper will provide identification and information about the social changes that are taking place in this new era, caused by Covid-19. Various images that show social behavior or attitudes after the Covid-19 pandemic, as well as sharing information on various media platforms can be obtained with the right information. The social changes that have occurred in society in the new normal era have become an issue of the social system which is currently being widely discussed in order to suppress the corona virus and the various impacts it has caused. The new normal era can be said to have been well achieved if it is able to go beyond various evaluations and indicators that have been measured to be able to collaborate with components of 21st century society.